Collaborative Governance in the Development of Salatiga as a Creative City of Gastronomy - Dina, Sopia; Hadiwijoyo, Suryo Sakti; Fretes, Christian H.J de (Journal of Management and Administration Provision, 2025)
Gastronomy is not only related to food, but also encompasses cultural values, history, local identity, and community creativity. In the context of creative city development, gastronomy is considered a strategic sector as it can stimulate local economic growth, strengthen regional identity, and support sustainable tourism. Salatiga, a small city known as a "mini city," has a diverse range of legendary culinary traditions, including ten locally recognized culinary heritage items. This research aims to analyze the processes and mechanisms of collaborative governance in promoting Salatiga’s culinary sector as a sustainable tourist attraction. The research method used is qualitative with a descriptive approach. Data were collected through observation, interviews, and literature studies related to creative city development policies and programs. The results indicate that the development of the gastronomic sector in Salatiga is supported by collaboration among government bodies, academics, business actors, communities, and the private sector. Several strategic policies have been implemented, such as the recognition of local culinary specialties as intangible cultural heritage, culinary innovation training for business actors, and the integration of gastronomy into the basic education curriculum. However, the implementation of collaborative governance faces several challenges, including suboptimal cross-sector coordination and a limited public understanding of gastronomy. This study concludes that collaborative governance plays a key role in the development of Salatiga as a UNESCO Creative City of Gastronomy. The success of this approach is reflected in the ASEAN Sustainable Tourism Award 2024 and the formal recognition of culinary heritage, which enhances Salatiga’s global competitiveness.